2006
DOI: 10.1007/s11104-006-9083-6
|View full text |Cite
|
Sign up to set email alerts
|

Soil-mixing effects on inorganic nitrogen production and consumption in forest and shrubland soils

Abstract: Soils that are physically disturbed are often reported to show net nitrification and NO 3 -loss. To investigate the response of soil N cycling rates to soil mixing, we assayed gross rates of mineralization, nitrification, NH 4 + consumption, and NO 3 -consumption in a suite of soils from eleven woody plant communities in Oregon, New Mexico, and Utah. Results suggest that the common response of net NO 3 -flux from disturbed soils is not a straightforward response of increased gross nitrification, but instead ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…Soil mixing can alter gross rates of N mineralization and nitrification (Booth et al, 2006;Kaur et al, 2010;Schimel et al, 1989). It is thought that mixing breaks up soil aggregates to release physically protected organic matter, thereby increasing substrate availability for mineralization to stimulate gross N mineralization rates (Booth et al, 2006;Schimel et al, 1989). The gross N mineralization rates we observed were within the range of values reported in the Booth et al (2005) meta-analysis, which found no significant difference in rates documented in studies using intact versus mixed soils.…”
Section: Methodological Considerationssupporting
confidence: 67%
See 3 more Smart Citations
“…Soil mixing can alter gross rates of N mineralization and nitrification (Booth et al, 2006;Kaur et al, 2010;Schimel et al, 1989). It is thought that mixing breaks up soil aggregates to release physically protected organic matter, thereby increasing substrate availability for mineralization to stimulate gross N mineralization rates (Booth et al, 2006;Schimel et al, 1989). The gross N mineralization rates we observed were within the range of values reported in the Booth et al (2005) meta-analysis, which found no significant difference in rates documented in studies using intact versus mixed soils.…”
Section: Methodological Considerationssupporting
confidence: 67%
“…Third, we used gently mixed (i.e., not sieved) soil for the assays to allow us to relate multiple N cycling processes and soil properties to the same homogenous soil sample, facilitating our objective to correlate these variables with each other. Soil mixing can alter gross rates of N mineralization and nitrification (Booth et al, 2006;Kaur et al, 2010;Schimel et al, 1989). It is thought that mixing breaks up soil aggregates to release physically protected organic matter, thereby increasing substrate availability for mineralization to stimulate gross N mineralization rates (Booth et al, 2006;Schimel et al, 1989).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrate production can be enhanced by soil disturbance, e.g., through tillage (Kristensen et al 2000) or when soil is placed inside cores (Ross and Hales 2003;Booth et al 2006). Simply collecting soil samples for later chemical analysis can also result in considerable increases in ammonium and nitrate concentrations within hours of removal from the field (Turner and Romero 2009).…”
Section: Soil Conditioner Effects In Contextmentioning
confidence: 99%